Selective C‐Reactive Protein‐Apheresis in Patients. Issue 6 (29th April 2019) - Ries, Wolfgang; Heigl, Franz; Garlichs, Christoph; Sheriff, Ahmed; Torzewski, Jan
Abstract: C‐reactive protein (CRP), the prototype human acute‐phase protein, is a well‐known marker of inflammation. However, CRP may also mediate tissue damage in various human diseases like atherosclerosis, acute myocardial infarction, dilated cardiomyopathy, stroke, and potentially autoimmune disease. Therefore, CRP elimination from human plasma may indeed be a widely usable therapeutic approach. Recently, a first‐in‐man case report of selective CRP‐apheresis in a patient with acute ST‐segment elevation myocardial infarction (STEMI) has been published. Here, the method is further elucidated by detailed description of 13 patients receiving CRP‐apheresis at two study centers. Thirteen patients received two sequential CRP‐apheresis treatments with the PentraSorb CRP adsorber starting 24 ± 12 h after STEMI and successful percutaneous coronary intervention (PCI). CRP was measured immediately before and after each treatment, and additionally twice a day for a period of 96 h after symptom onset. Compared to the initial (before‐treatment) CRP plasma concentration, CRP‐apheresis resulted in an average 53.4% ± 11.9% CRP depletion. First apheresis was performed 27.5 ± 4.6 h after symptom onset at a mean CRP concentration of 25.1 ± 11.1 mg/L. Mean CRP concentration after the first treatment was 12.1 ± 6.4 mg/L. Second apheresis started 47.9 ± 5.4 h after symptom onset at a mean CRP concentration of 30.2 ± 21.4 mg/L. After the second treatment, mean CRP concentration was reduced to 13.9 ± 10.9 mg/L. No severe apheresis‐associated side effects were observed. Patients tolerated selective CRP‐apheresis without any side effects. The new method is feasible and safe and significantly reduces CRP plasma concentration in humans.